KINETIC MODELING STUDY FOR ACYLATION REACTION OF O-XYLENE TO 3,4-DIMETHYLBENZOPHENONE OVER H-BETA - -, Yusnimar (Jurnal Riset Kimia, 2007)
ABSTRACTThe reaction of o-xylene with benzoic anhydride has been studied by the changing molar ratio of the reactants (20:1, 10:1, and 5:1) in a batch reactor under reaction temperature 120oC. The reaction carried out without catalyst and also with catalyst Zeolite beta which was activated at 300oC overnight. HPLC analysis results showed that the yield of the product increase with the changing molar ratio of the reactants. An attempt was made in determining the kinetics of the reaction. The results show that the reaction is neither first nor second order in the acylating agent. Obtaining the reaction order even initially is unsuitable for even simple reactions that do not go to completion. It is even less applicable where more than a single process which affects the rate is taking place right from the start. These might be any one or combination of diffusion, adsorption, desorption, inhibition of the reaction by the product and multi step reactions on the surface. Postulated reaction mechanisms may be required in combination with experimental data to determine even initial reaction orders. Key words: o-xylene, catalyst, kinetics, reaction order.